Instruments of Production Functions as Reserves of Increase in Regional Tax Revenues - Dzhurbina, Elena M.; Fateev, Dmitriy I. (International Journal of Economics and Financial Issues, 2016)
The article is devoted to the quantitative analysis of the possibilities to increase tax revenues of the regions of the North Caucasus Federal District of the Russian Federation on the basis of more efficient use of the available factors of production – labor and capital. Successfully verified approach of production functions enables to use their potential in order to study the reserves of increase in tax revenues of budgets of all levels and quantitatively substantiate their priorities as well as the prospects of regional economic policy. Keywords: tax revenues, gross regional product, production function, factors of production, regional economy JEL Classifications: C21, H71, R10